Beyond the formation of foreign subsidiaries: Why do MNEs divest them? - Sormunen, Eero (My University, 2026)
Foreign subsidiaries are frequently stated to be popular but with high divestment rates. Therefore, a great deal of attention has been paid to investigating the determinants of foreign subsidiary divestment. However, prior research does not provide a comprehensive understanding of factors driving foreign subsidiary divestment. Therefore, the main objective of this thesis to investigate the factors which lead the multinational enterprises (MNEs) to divest their foreign subsidiaries. The conceptual framework of this thesis is developed by reviewing the existing literature on motives and characteristics of foreign subsidiaries, divestment and modes of foreign subsidiary divestment, and determinants of foreign subsidiary divestment. The findings suggest that foreign parent size, target country experience, and subsidiary's intangible resource relatedness with MNE reduce the divestment likelihood of foreign subsidiary. Findings further suggest that acquisition establishment mode, poor financial performance of foreign subsidiary, subsidiary's product relatedness with MNE, political risk in target country, economic nationalism and protectionism of target country, and cultural distance enhance the divestment likelihood of foreign subsidiary. These findings have important implications for subsidiary managers to understand the factors leading to divestment of foreign subsidiary. Monikansallisten yhtiöiden ulkomaiset tytäryhtiöt ovat suosittu tapa laajentaa liiketoimintaa, mutta kohtaavat suuren divestoinnin (omistuksesta luopumisen) riskin ulkomailla. Kyseisen riskin syitä on tutkittu monipuolisesti, mutta tehty tutkimus ei kykene tarjoamaan laaja-alaista ymmärrystä kaikille niille syille, jotka ajavat tytäryhtiöitä kohti omistuksesta luopumista. Tämän opinnäytetyön tavoite on tutkia niitä syitä, jotka johtavat monikansallisten yhtiöiden päätökseen divestoida tytäryhtiönsä. Opinnäytetyön teoreettinen viitekehys on kehitetty käymällä läpi kirjallisuutta tytäryhtiöistä, niiden motiiveista sekä divestointitavoista ja -syistä. Löydökset osoittavat, että tytäryhtiön emoyhtiön koko ja kansainvälinen kokemus sekä tytäryhtiön aineettomien resurssien samankaltaisuus emoyhtiön kanssa vähentävät divestoinnin todennäköisyyttä. Löydökset osoittavat myös, että tytäryhtiön perustaminen yritysoston kautta, tytäryhtiön heikko taloudellinen suorituskyky, tytäryhtiön tuotteiden samankaltaisuus emoyhtiön kanssa, kohdemaan poliittinen riski, talousnationalismi ja protektionismi sekä kulttuurillinen etäisyys lisäävät divestoinnin todennäköisyyttä. Näillä löydöksillä on tärkeä merkitys tytäryhtiöiden johtajille ulkomaisen tytäryhtiön divestointiin johtavien tekijöiden ymmärtämiseksi.
Keywords: subsidiary companies; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|